Otitis-prone children produce functional antibodies to pneumolysin and pneumococcal polysaccharides - Kirkham, L.; Wiertsema, S.; Corscadden, K.; Mateus, T.; Mullaney, G.; Zhang, Guicheng; Richmond, P.; Thornton, R. (2017)
Copyright © 2017 Kirkham et al. The pneumococcus is a major otitis media (OM) pathogen, but data are conflicting regarding whether otitis-prone children have impaired humoral immunity to pneumococcal antigens. We and others have shown that otitis-prone and healthy children have similar antibody titers to pneumococcal proteins and polysaccharides (vaccine and nonvaccine types); however, the quality of antibodies from otitis-prone children has not been investigated. Antibody function, rather than titer, is considered to be a better correlate of protection from pneumococcal disease. Therefore, we compared the capacities of antibodies from otitis-prone (cases) and healthy (controls) children to neutralize pneumolysin, the pneumococcal toxin currently in development as a vaccine antigen, and to opsonize pneumococcal vaccine and nonvaccine serotypes. A pneumolysin neutralization assay was conducted on cholesterol-depleted complementinactivated sera from 165 cases and 61 controls. A multiplex opsonophagocytosis assay (MOPA) was conducted on sera from 20 cases and 20 controls. Neutralizing and opsonizing titers were calculated with antigen-specific IgG titers to determine antibody potency for pneumolysin, pneumococcal conjugate vaccine (PCV) polysaccharides, and non-PCV polysaccharides. There was no significant difference in antibody potencies between cases and controls for the antigens tested. Antipneumolysin neutralizing titers increased with the number of episodes of acute OM, but antibody potency did not. Pneumolysin antibody potency was lower in children colonized with pneumococci than in noncarriers, and this was significant for the otitis-prone group (P < 0.05). The production of functional antipneumococcal antibodies in otitisprone children demonstrates that they respond to the current PCV and are likely to respond to pneumolysin-based vaccines as effectively as healthy children.